DOES THE NUMBER OF SUPERVISED COUNSELING PRACTICE EXPERIENCES MAKE DIFFERENCE IN THE WISDOM OF PRE-SERVICE COUNSELORS? - Agus Taufiq; Herdi Herdi (LPMPP Universitas Negeri Yogyakarta, 2020)
Wisdom is one of the fundamental qualities of personality, core competence, and predictors of effective counselor. The wisdom of a pre-service counselor is predicted to develop if the counselor has the opportunity to undergo, ask, reflect, and internalize his/her experiences through supervised counseling practice. The objective of the research is to compare the wisdom resulted by Indonesian pre-service counselors based on the number of supervision during counseling practices. The research used the ex post facto method. The sample of this research consisted of 489 sixth semester pre-service counselors of 11 guidance and counseling department in Indonesia, whereas 307 students only received 3x supervision, and 182 students with 3x supervision. Data were collected using Indonesian Counselor's Wisdom Scale with Cronbach’s Alpha = .92. The t-test results show that there was a significant difference in the average score of wisdom and each dimension: religious, personal, social, emotional, reflective, and ethic of the pre-service counselors based on the number of supervised counseling practice where those with less supervision had better quality of wisdom. This means that the small number of supervised counseling practice experience but with a quality of supervisory working alliance can develop the wisdom of pre-service counselors.